Algorithms and data structures in Python : an overview. (Manning Publications, 2022)
In this video, Kyle demonstrates how to write programs to help users analyze housing data. You'll learn to read and write CSV files, and you'll implement algorithms to efficiently sort, search through, and de-duplicate the data.